BCPT: Participant Update - K. Smigel (JNCI Journal of the National Cancer Institute, 1994)
Introduction Poisoning with ethylene glycol and methanol remains a recurrent problem in Scandinavia. This study aimed to describe the epidemiology, exposure circumstances, clinical characteristics and management of toxic alcohol poisonings reported to the Danish Poison Information Centre to support preventive initiatives and improve toxicological counselling. Methods All calls concerning confirmed or suspected ingestion of ethylene glycol or methanol registered by the Danish Poison Information Centre between 2006 and 2022 were reviewed. Results A total of 592 exposures involving ethylene glycol (85%) or methanol were identified. Children accounted for 25% of exposures and adults for 61%, with a predominance of males (73%). Accidental ingestion accounted for 71% of exposures. In more than 60% of cases, the Danish Poison Information Centre assessed a risk of moderate to potentially fatal poisoning. Hospitalization was recommended in approximately 70% of cases. Discussion Ethylene glycol poisoning was more common than methanol poisoning and was primarily associated with accidental ingestion of engine coolant products following inappropriate storage or handling. Many patients were referred for hospital evaluation because risk assessment relied mainly on circumstantial information suggesting potential severe poisoning. Conclusions Toxic alcohol poisoning in Denmark is primarily caused by accidental ethylene glycol ingestion. Rapid blood analysis of toxic alcohols may reduce delayed treatment and unnecessary hospitalization.